Big vs Small Data in Micro and Small Companies - Cekerevac, Zoran; Dvorak, Zdenek; Prigoda, Ludmila; Cekerevac, Petar (Communications - Scientific letters of the University of Zilina, 2016)
This article deals with the challenges that are faced by micro and small enterprises using data. After naming main hypotheses of the research, the attention is paid to definitions of big and small data and to their comparison. In the paper, analyses of the connections between big data and Internet are given. The main attention is paid to the use of big data in micro and small enterprises through the analyses of needed skills, organizational changes and big data management including possible pros and cons. As a special item, the analysis of risks and implementation is given. The analyses are supported with a lot of research results and numerous literature sources. At the end of the article there are conclusions about directions how micro and small enterprises should use big data and how to invest rationally in big data.